2015
DOI: 10.3923/tmr.2015.63.68
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fasting on Intestinal Motility and Transit in Albino Wistar Rats

Abstract: Fasting is the act of willingly abstaining from some or all probable kinds of food, drinks or both for a period of time. Knowledge of the effect of fasting on intestinal motility and transit is incomprehensible, this study, therefore, seeks to ascertain the effect of fasting on intestinal motility and intestinal transit. Twelve albino wistar rats of body weight ranging between 160-200 g were used. These rats were randomly assigned into 2 groups, control and test (fasted) with six rats each. Both groups were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Food consumption induces dynamic changes in the GI tract (Varum et al, 2013;Abuhelwa et al, 2017;O'Shea et al, 2018) including luminal fluid volume and composition, and patterns of intestinal motility which ultimately affect the transit time of dosage forms (Ofutet et al, 2015;Ibekwe et al, 2008;Fadda et al, 2009;Liu et al, 2009). The understanding of the influence of food on P-gp expression in rodents, its potential difference between sexes and its implications for oral drug delivery are still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Food consumption induces dynamic changes in the GI tract (Varum et al, 2013;Abuhelwa et al, 2017;O'Shea et al, 2018) including luminal fluid volume and composition, and patterns of intestinal motility which ultimately affect the transit time of dosage forms (Ofutet et al, 2015;Ibekwe et al, 2008;Fadda et al, 2009;Liu et al, 2009). The understanding of the influence of food on P-gp expression in rodents, its potential difference between sexes and its implications for oral drug delivery are still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that acute fasting or restricted energy intake may have a direct or indirect effect on gastrointestinal motility through satiety hormones ( 31 33 ). In our Cx3cr1-Dtr rats, we have consistently reported a decrease in body weight ( Figure 2A ) as well as food intake ( 17 ) upon DT injection.…”
Section: Resultsmentioning
confidence: 99%